PENGARUH TERAPI ROM EKSTREMITAS BAWAH TERHADAP PEMULIHAN PERISTALTIK USUS PADA PASIEN POST OPERASI SECTIO CAESAREA DI RS BHAYANGKARA MANADO - Lolaroh, Fanda (Journal Of Community & Emergency, 2024)
Sectio Caesarea is an action to remove the fetus through an incision. ROM is one of the measures to accelerate the recovery of intestinal peristalsis in post-operative patients. This study aims to determine whether there is “The Effect of Lower Extremity Rom Therapy on the Recovery of Intestinal Peristalsis in Patients with Post Csection Surgery at Bhayangkara Hospital Manado. This study used a pre-experimental method with a one-group pretest-posttest design. The population of this study were postoperative sectio caesarea patients and the sample used was 16 respondents. T-test results obtained p value = 0.000 <0.05 so that there is an effect of lower extremity ROM therapy on the recovery of intestinal peristalsis in postoperative sectio caesarea patients at Bhayangkara Hospital Manado.